Comparative Clinical Efficacy Of Vaitarana Basti And Kshar Basti In The Management Of Aamvata W.S.R To Rheumatoid Arthritis (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda, the ancient system of medicine from India, has gained worldwide recognition for its holistic approach to health and well-being. With the changing dietary habits, lifestyle, and environment, the occurrence of diseases like Amavata (Rheumatoid Arthritis) has increased. Amavata is a chronic inflammatory joint disease characterized by swollen, painful, and stiff joints, causing significant morbidity and physical impairment, particularly in women.The formation of Ama, a toxic substance resulting from impaired digestion and metabolism, plays a crucial role in the pathogenesis of Amavata. Ama can obstruct the body's channels and manifest locally or systemically, leading to various signs and symptoms of the disease. Ama and Vata are the primary pathological factors in Amavata, with Kapha and Pitta also involved in its development.In modern treatment approaches, patients often seek alternative medicine, such as Ayurveda, to alleviate pain and minimize side effects. Ayurvedic texts like Madhava Nidana, Chakrapanidatta, and Yogaratnakara extensively describe Amavata, which can be correlated with Rheumatoid Arthritis. Ayurvedic treatment strategies for Amavata include fasting, sudation, ingestion of bitter and pungent tastes, purgation, oleation, enema, and dry fomentation.Considering the above facts, this research project titled "Comparative Clinical Efficacy of Vaitarana Basti and Kshar Basti in the Management of Aamvata (Rheumatoid Arthritis)" was conducted to explore the effectiveness of specific Ayurvedic treatments. The results of the study were promising, providing hope for future generations in the management of this debilitating condition.